2010
DOI: 10.1245/s10434-010-1266-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preoperative Magnetic Resonance Imaging for Invasive Lobular Cancer: Good, Better, but Maybe not the Best?

Abstract: For ILC, MRI has better sensitivity of detection and correlation with tumor size at pathology than CBE, mammography, or ultrasound. However, 31% of cases are overestimated by MRI, and correlation remains only at 0.75. The select use of MRI for preoperative estimation of tumor size in ILC is supported by our data, but the need for improvement and refinement of imaging remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 42 publications
6
36
2
1
Order By: Relevance
“…Limits within which measurements on MRI are considered concordant with measurements at pathology vary and range from 0 mm -20 mm [11,[24][25][26][27]. We used a limit of 10 mm to define concordance and Bland Altman plots to measure systematic and random differences.…”
Section: Discussionmentioning
confidence: 99%
“…Limits within which measurements on MRI are considered concordant with measurements at pathology vary and range from 0 mm -20 mm [11,[24][25][26][27]. We used a limit of 10 mm to define concordance and Bland Altman plots to measure systematic and random differences.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative breast MRI has been found to be highly sensitive in detecting lesions not seen using mammography or ultrasound among patients with ILC [17]. However, only a few studies have examined the association between breast MRI and surgical outcomes in women with ILC [5, 18-20]. These studies were limited in that they were single institution studies [18-20] and an RCT from the United Kingdom[5] with a small number of ILC patients from settings with distinct surgical treatment patterns, health service resources, and insurance structures that may not be generalizable to the US elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…This preoperative tool reduces the need for re-excision after BCS 22,23 . However, a recent meta-analysis has demonstrated that preoperative MRI potentially increases the mastectomy ratio 24 .…”
Section: Discussionmentioning
confidence: 99%